Thiol–Ene "Click" Reaction Triggered by Neutral Ionic Liquid: The "Ambiphilic" Character of [hmim]Br in the Regioselective Nucleophilic Hydrothiolation1. Issue 3 (27th November 2014) - Kumar, Rajesh; Saima; Shard, Amit; Andhare, Nitin H.; Richa; Sinha, Arun K.
Abstract Thiol–ene "click" chemistry has emerged as a powerful strategy to construct carbon–heteroatom (CS) bonds, which generally results in the formation of two regioisomers. To this end, the neutral ionic liquid [hmim]Br has been explored as a solvent cum catalyst for the synthesis of linear thioethers from activated and inactivated styrene derivatives or secondary benzyl alcohols and thiols without the requirement of using a metal complex, base, or free radical initiator. Furthermore, detailed mechanistic investigations using 1H NMR spectroscopy and quadrupole time‐of‐flight electrospray ionization mass spectrometry (Q‐TOF ESI‐MS) revealed that the "ambiphilic" character of the ionic liquid promotes the nucleophilic addition of thiol to styrene through an anti‐Markovnikov pathway. The catalyst recyclability and the extension of the methodology for thiol–yne click chemistry are additional benefits. A competitive study among thiophenol, styrene, and phenyl acetylene revealed that the rate of reaction is in the order of thiol–yne>thiol–ene>dimerization of thiol in [hmim]Br.